A Comparative Study of Anxiety, Pain and Maternal-fetal Attachment between Women who became Pregnant after Infertility Treatment and became Pregnant Naturally - Hee Ja Yoon; Seung Shin Lee; Song Hee Ye; Ah Reum Han; So Ri Lim; Hyun Jung Chung; Jum Mi Park (Korean Journal of Women Health Nursing, 2016)
PURPOSE: This study was a comparative study to understand the levels of anxiety, pain and maternal-fetal attachment between women who became pregnant after infertility treatment and became pregnant naturally. METHODS: This study used a comparative survey design. Data were collected by 50 couples of natural pregnancy and of who became pregnant after infertility treatment who visited delivery room in C Medical hospital, Seoul. These couples were to have first baby, and cervix dilatation of women was less than 3 cm regardless of diagnosis. RESULTS: The score of anxiety of infertile women was significantly higher than that of naturally pregnant women; however, that of spouses showed no difference. The pain score for infertile women was significantly higher in both the active and transition phases. Pain scores that reported by their spouses did not show differences in either phase. The score of maternal-fetal attachment showed no difference between two groups of women. CONCLUSION: The result showed the importance of nursing intervention to reduce women's anxiety and pain, through both antenatal-childbirth education programs and assertive nursing interventions. It is necessary to develop and evaluate new intervention which would be more effective for reducing pain and anxiety for couples who became pregnant after infertility treatment.